Identifying the source of incumbency advantage through an electoral reform - Mariana Lopes da Fonseca (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This study relies on a constitutional reform introducing term limits at the local elections level in Portugal as a natural experiment to estimate incumbency advantage in mayoral elections. It stresses the distinction between partisan and personal incumbency advantage using data on six local elections in 278 homogenous municipalities from 1993 to 2013. The analysis is based on two quasi-experimental methods, the RD and diff-in-disc designs, that allow for credible inference upon the source and magnitude of the incumbency advantage. Main contributions include one of the first estimates of partisan incumbency advantage in the literature and the use of a novel method in its estimation. Results show that whilst the returns to incumbency accruing to the candidate are positive and significant, there is no evidence of a significant partisan incumbency advantage. In addition, robustness test point to a potential role of term limits in causing political turnover.
Keywords: D70; D72; D78; 330; incumbency advantage; local politics; electoral reform